2020
DOI: 10.34172/jlms.2020.28
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Implant Placement in Infected Sockets: A Consecutive Cohort Study

Abstract: Introduction: Immediate placement of implants in a fresh post-extraction socket is an increasingly popular and established treatment option. However, active infection in the extraction site may adversely affect the outcome of this procedure. This study was designed to assess the clinical results of immediate placement of dental implants in infected extraction sockets using a standardized protocol, which included (a) the use of an Er,Cr:YSGG laser for the decontamination of the infected socket prior to implant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 36 publications
(46 reference statements)
0
15
0
Order By: Relevance
“…In a recent publication by Kakar et al, the authors followed a clinical protocol similar to the present study, including debridement with Er,Cr:YSGG 2780 nm laser, to treat a case series without a control group [ 19 ]. However, despite the lack of measurements of the MBL, the highlight of the study was that the survival of the implants exceeded 95%, which is in line with the survival rate expected from conventional implantology methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent publication by Kakar et al, the authors followed a clinical protocol similar to the present study, including debridement with Er,Cr:YSGG 2780 nm laser, to treat a case series without a control group [ 19 ]. However, despite the lack of measurements of the MBL, the highlight of the study was that the survival of the implants exceeded 95%, which is in line with the survival rate expected from conventional implantology methods.…”
Section: Discussionmentioning
confidence: 99%
“…Kusek presented the first case series, which included 10 immediate implantation [16]. Later, other authors carried out independent research illustrating the use of Er,Cr:YSGG laser to treat dental alveoli [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Recent findings suggest that immediate implant placement in infected socket sites is not associated with inferior implant survival rates or increased risks compared to noninfected sites. [ 15 ] However, thorough debridement and decontamination of hard and soft tissues and removal of microbial debris are prerequisites for successful immediate implant placement. [ 15 ] It is suggested that laser can be used for debridement of extraction sockets during immediate implant placement.…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 ] However, thorough debridement and decontamination of hard and soft tissues and removal of microbial debris are prerequisites for successful immediate implant placement. [ 15 ] It is suggested that laser can be used for debridement of extraction sockets during immediate implant placement. [ 16 ] The present case awakens the practitioners to be cautious regarding long-standing periodontal and periapical pathologies, which may interfere in treatment outcomes of immediate implant placement.…”
Section: Discussionmentioning
confidence: 99%
“…Although postextraction implant placement has been widely validated, few studies have reported results at infected sites during the healing process. Some studies have described the use of erbium, chromium-doped yttrium, scandium, gallium, and garnet (Er,Cr : YSGG) laser therapy to disinfect infectious processes, which can reduce treatment time [ 15 ].…”
Section: Discussionmentioning
confidence: 99%